The Correlations of the Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio with Bone Mineral Density in Postmenopausal Women: A Cross-Sectional Study - Pierpaolo Panebianco; Gianluca Testa; Giulia Barbagallo; Luciano Costarella; Alessia Caldaci; Sveva Condorelli; Marco Sapienza; Vito Pavone (Osteology, 2025)
Background/Objectives: Osteoporosis is a skeletal disorder characterized by reduced bone mineral density (BMD) and increased fracture risk. Chronic inflammation is implicated in osteoporosis pathogenesis, with inflammatory mediators promoting bone resorption. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are markers of systemic inflammation and have emerged as potential indicators of bone health. This study’s aim was to highlight the potential role of the NLR and PLR as markers of bone health in postmenopausal women affected by osteoporosis or osteopenia and to evaluate the possible influence of autoimmune disease in this context. Methods: This cross-sectional study included 124 postmenopausal women diagnosed with osteopenia or osteoporosis at the Orthopedic Unit of the Policlinico G. Rodolico in Catania, Italy. Demographic, clinical, laboratory, and diagnostic imaging data were collected. The NLR and PLR were calculated from complete blood counts, and BMD was measured using dual-energy X-ray absorptiometry (DEXA). Statistical analyses included correlations, group comparisons, and multiple and logistic regressions. Results: The NLR and PLR did not directly correlate with BMD or fracture incidence. However, the PLR weakly correlated with vitamin D levels. Notably, women without Hashimoto’s thyroiditis exhibited higher NLR values than those with the condition. Hypertensive women had a lower PLR than non-hypertensive women, while euthyroid women had a higher PLR than hyperthyroid or hypothyroid women. Multiple regression analysis revealed that age, BMI, CKD stage, vitamin D levels, NLR, PLR, diabetes, and autoimmune diseases significantly predicted BMD at the femur neck, with the PLR contributing significantly. Logistic regression confirmed these predictors for osteoporosis or osteopenia, with an increased PLR being associated with a higher likelihood of osteoporosis. Conclusions: While the NLR and PLR may not independently predict bone health, their inclusion in a multifactorial assessment considering age, BMI, vitamin D, and comorbidities could enhance osteoporosis management.